THE PROCESS OF STATE REGULATION OF BUSINESS - Abduvokhidov Akmal Abdulazizovich; PhD., Obilov Mirkomil Rashidovich; Eshpulatov Dostonbek Bakhodir ogli (Scholar Express Journals, 2022)
This article analyzes the necessity, directions, levers, and methods of state regulation of business activities in the national economy, as well as the process of improving state regulation
Keywords: Entrepreneurship; regulatory methods; entrepreneurial subject; entrepreneur's right